Gebrauchsmusik as Wartime Exile Response: Hanns Eisler’s Woodbury Liederbüchlein: Paper from the conference: Neue Sachlichkeit, Political Music, or Vernacular Avant-Garde? Hanns Eisler and his Contemporaries - Caleb, Boyd (Danish Yearbook of Musicology, 2019)
Hanns Eisler spent summer 1941 in Woodbury, Connecticut at the home of philosopher Joachim Schumacher, a lecturer at the nearby Westover School, an academic institution for young girls. That summer, Eisler wrote his Woodbury Liederbüchlein, a collection of twenty short a cappella songs for the Westover glee club. He used familiar children’s rhymes to teach young singers various choral styles associated with American amateur glee performance, while also introducing young voices to contemporary musical language. However, news of Hitler’s invasion of the Soviet Union that summer darkened Eisler’s spirit, prompting him to include four austere German-language reactions. Therefore, the Woodbury Liederbüchlein serves a dual purpose as Gebrauchsmusik for maturing singers and as an exile’s artistic reaction to the existential horrors of war. Eisler scholars such as Jürgen Schebera and Albrecht Dümling have addressed the collection’s contradictory character, with particular interest directed toward the German songs. Eisler’s original intention for these songs as instructional pieces for amateur female choir has been overlooked. This article draws upon research at the Hanns Eisler Papers at the University of Southern California, the Joachim Schumacher Papers at the University of Connecticut, and the archives at the Westover School in Middlebury, Connecticut.